ABOUT THE WORK "HULOSHAT AL-AHWAL" (Scientific journal of the Fergana State University, 2024)
This article interprets the work of the historian Abu Ubaydullah, who lived in the Kokand Khanate, “Khulosat ul-ahwol” as a memoir source. Basically, the analysis involved information from the work related to the authorʼs position as a tax collector and illuminating some aspects of the socio-political life of the Khanate.